Social dimensions of economic development and productivity : inequality and social performance - Carlson, Beverley A. (ECLAC SantiagoCL, 1999)
Deals with various aspects of the challenge of improving social performance, inequality and poverty, including the problems that arise from the special characteristics of Latin American society. Presents papers on demography, income distribution, culture, poverty indicators and education.